Pelatihan Pemilahan Sampah bagi Pemuda Karang Taruna Fajar Menyingsing Kelurahan Balai Gadang Koto Tangah Kota Padang - Suryadimal; Yeasy Darmayanti; Kaidir; Saddam Husain; Aldo Nasvipratama; Luthfi Nabilla Ditri (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2024)
Waste sorting activities are carried out by all parties without exception, including the community in Balai Gadang District. As the vanguard in maintaining cleanliness, the elements of society in Karang Taruna are the parties who are always educated regarding waste sorting. The method used is through waste sorting training so that it can solve the community's waste problems, the training given to Karang Taruna can also provide welfare for them, because several types of waste can be resold to collectors. This activity is a series of programs from the LPPM Universitas Bung Hatta, in collaboration with Balai Gadang Urban Village, Padang City as a concern for waste management in Padang City. The targets achieved are two programs that will be implemented, namely: 1). Waste sorting training as a positive mindset for the community about the dangers of waste, and 2). Waste training for cleaning officers of the Karang Taruna Fajar Menyingsing LPS. The results of the community service program showed an increase in understanding of waste sorting by 92% and waste management methods by 85% and the impact of littering an average of 89%.